Teaching, learning and performing approaches for classical guitar and piano : A case study at an institute of higher learning in Malaysia - Lok, Lay Hong (2014)
This is an in-depth study on methodological procedures where different learning theories are posited through the incorporation of self-formative processes or using collaborative pedagogue techniques. The aim and purpose of this study is to establish a robust framework of teaching, learning and performing approaches for classical guitar and piano at tertiary level. It examined the direction and ownership of a tri-partite hierarchy framework in this case study. The study also served to induce reflective considerations around the concepts of innovative solutions and musical practices in teaching, learning and performing. The intent was to manifest the pathways of approaches that foster a disposition of exercising creativity and innovation through the engagement of students in meaningful musical development and achievements. This study was indebted to 52 respondents and four non-participant observers who had responded to 75 interviews scheduled. Qualitative methods were employed and interviews were carried out for a year, video and tape recorded, transcribed, coded, analysed and articulated in writing. The most common rationale or views selected by respondents were their sense for competency, liberation and recognition of viable and dynamic approaches to teaching, learning and performing process. It was revealed that the expression of respondents’ critical consciousness and musical experiences were the manifestation of thoughts and ideas through macro and micro treatment from various observational settings and interviews. Findings suggested that there were extrinsic justifications to fulfill the clear need of reflexive pedagogy approaches to teaching, learning and performing practices. A retooling curricular connection to formalise and support the study of classical guitar and piano is warranted. A hierarchical construction to experience the said approaches was established by empowering students to engage in literate and nonliterate playing. Audiation methods based on their innate musical intelligence amidst “shared and agreed” aims were employed. These are imperatives of experiencebased and personal teaching and learning beliefs propounded in this study.